Pengaruh Kepemimpinan Terhadap Disiplin Kerja Karyawan PT. Bringin Karya Sejahtera Building Management Pekanbaru - Nova Syafrina; Warman Aditya (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This research was conducted at PT. Bringin Karya Sejahtera BuildingManagement Pekanbaru. The purpose of this study was to determine the effect ofleadership on employee work discipline. The population in this study was 50 people.In this study, a saturated sample of 48 people was used because reseachers andleader were not included in the sample, The dlata used were primary and secondary data with analysis using simple linear regression. The results showed that the datawas valid, reliable, and normally distributed. And the results of the linear regressionwere Y=11.775+0.557X which had a positive relationship direction, and theleadership variable had a significant effect on work discipline, this can be seen fromthe t_count valuetable (6.242> 2.0129). Meanwhile, the magnitude of theleadership on work discipline is 45.9% while the remaining 54.1% is influenced byother independent variables not examined in this study, such as the workenvironment and supervision.